Management of Mandibular Fracture in Paediatric Patients at L.U.H Hyderabad (Medical Forum Monthly, 2024)
Objective: The study was conducted to analyze the different treatment options practiced in pediatric mandibular fracture patients at L.U.H Hyderabad.Introduction: Maxillofacial fractures are infrequent in the pediatric population, and their treatment is unique due to the psychological, physiological, developmental and anatomical characteristics of children. Besides this it is difficult to examine child both clinically and radiographically. Study Design: Retrospective StudyPlace and Duration of Study: This study was carried out in Department of oral and maxillofacial surgery L.U.H Hyderabad for a period of two years i.e. from June 2010 to June 2012.Materials and Methods: Gender distribution Total 180 patients, 118 patients (65.6%) were males and 62 patients (34.4%) were females. Most common site involved was parasymphysis, involved in 85 (47%), in other sites angle in 43 (23%), condyle 25 (13%)cases, symphysis 15 (8%), body 10 (5%) and ramus in 2(1%).Results: Most of the patients were treated with IMF with arch bar i.e 75 (41%). Clearer understanding of paediatric pattern of mandibular fractures will help out health care providers as they plan and manage the treatment of mandible fractures in children.Conclusion: The most common site involved in these patients is mandibular parasymphysis. Clearer understanding of pediatric pattern of mandible fractures will help out oral maxillofacial surgeon as they plan and manage the treatment of mandible fractures in children